Affective commitment through further training: the roles of firm provision and employee participation - Christian Grund; Krystina Titz (Review of Managerial Science, 2021)
This study investigates the relation of further training and employees' affective commitment by disentangling the relevance of a firm's general support for further training and the individual's actual participation. Using linked employer-employee data, we consider both the firm's and the individual's perspective and control for several HR instruments additionally to the usual demographics and job characteristics. We also distinguish between subgroups of employees regarding age and schooling. Results show that employees' participation in further training and a firm's support for further training are both positively related to affective commitment. Furthermore, our results hint for differences in employees' expectations regarding the amount of the firm's support for further training. Whereas there is no meaningful relation of the general firm's support for further training to commitment of university graduates, participation in further training measures and the individuals' perceived support for personnel development is particularly relevant for this group of employees.
Keywords: H15; 650; Commitment; Further training; Signalling; Linked employer-employee data